PENGARUH KONDISI KESEHATAN TERHADAP KONSENTRASI BELAJAR MAHASISWA KELAS D2 PRODI PGMI UIN KHAS JEMBER - Asri Ika Nurmaela, Lala (Jurnal Ilmiah Ibtida, 2023)
The purpose of this study was to determine whether there was a significant effect of health conditions on the learning concentration of D2 class students of the PGMI Study Program UIN KHAS Jember. Learning concentration can be influenced by health conditions. Health conditions are divided into 2, namely mental symptoms and physical symptoms. Mental symptoms include tiredness, hopelessness, tiredness, lethargy, and decreased concentration. While the physical symptoms such as difficulty sleeping, stress, headaches, dizziness, weakness and anxiety. This research is a quantitative causal comparative research. The population in this study amounted to 120 people and the sample was 30 people. The data collection method used is in the form of distributing questionnaires to D2 PGMI Class 2020 students, where the x variable is health condition and the y variable is learning concentration. The type of data in this study is a Likert scale. The analysis in this study uses simple linear regression. The results of the analysis in this study showed that F count = 1649.382 > F table = 1.701 with F table or Alpha = 0.05 > F Sig = 0.005, then Ha is accepted meaning that there is a significant influence between health conditions and the learning concentration of PGMI students.